Condiciones de vida y transporte. El caso del Subterráneo de Buenos Aires, 1900-1945 - Clichevsky, Nora (Revista EURE - Revista de Estudios Urbano Regionales, 1988)
The article shows the interrelations between the urban configuration of Buenos Aires and its transportation system, engaging on the historical background of that interrelation.